Performance Testing Of LPG-Fired Monotube Steam Generator - Tan, Zheng Heng (Universiti Sains Malaysia, 2017)
Small-sized steam generators are useful in power generation applications such as small scale power generation and utility purposes. The monotube boiler design is one of the safest designs available due to lower operating pressure and well-contained water tubes. In recent years, many optimizations have been done to improve boiler efficiency to reduce emissions and fuel usage. However most of the studies are done on larger boilers where the impact is most significant whereas studies on smaller boilers are few. This paper studies the performance of a specific monotube boiler in terms of efficiency and output. The efficiency and output are plotted against energy input to know the performance characteristics of the monotube boiler. Heat and mass balance was done as verification to the steam output data. It is determined that the specific design of monotube boiler have significant lower efficiency (15-18%) than conventional boilers. Modifications are needed to be made for the boiler to be feasible or commercial or practical usage. Index Terms – Monotube Boiler, Small-Scale Power Generation, Boiler Efficiency, Evaporation Ratio, Heat Balance